Identification of a novel regulator of extracellular matrix degradation in chondrocytes - Collins, I (2021)
There are currently no drugs that modify the progression of the degenerative joint disease osteoarthritis, which is characterised by protease-mediated degradation of the cartilage extracellular matrix. Identification of molecules that regulate protease activity could therefore lead to the development of new therapies for osteoarthritis. The Wann group previously showed that mutation of Intraflagellar transport protein 88 (IFT88) increased degradation of the cartilage matrix component aggrecan by proteases in vitro. As IFT88 is required for the assembly of a cell surface organelle called the primary cilium, the aim of my thesis was to investigate whether the primary cilium is involved in the regulation of protease activity. Based on the Wann group’s finding that mutation of IFT88 impaired Low-density lipoprotein receptor-related protein 1 (LRP-1)-mediated endocytosis of extracellular proteases, I hypothesised that the primary cilium is a region of efficient endocytosis and thus regulates the extracellular activity of proteases.